Selection of key indicators for reputation loss in oil and gas pipeline failure event. (May 2019) - Chen, Xuefeng; Wu, Zongzhi; Chen, Wentao; Kang, Rongxue; He, Xingzhen; Miao, Yongchun
Abstract: Pipeline is a safe and economical way to transport gas and oil. In the process of operation, third-party damage, corrosion destruction, design defect, misuse of factors and other unknown factors can cause pipeline failure, which pose a huge risk to life and property. To identify and develop strategies to prevent pipeline failure event, risk assessment and risk-based techniques are widely used in the oil and gas pipeline industry. However, although these methods and techniques can effectively prevent and reduce the tangible loss, i.e., human loss, production loss, asset loss and environmental loss, the intangible loss such as reputation loss is often neglected. This is not consistent with many current literature studies and actual situations. To address mentioned limitation, this article selected reputation loss indicators in pipeline failure event based on related literature and Delphi method, and the indicators are ranked by group making-decision method and fuzzy analytic hierarchy process (FAHP). The case study identified investor factor as dominant for reflecting reputation loss in oil and gas pipeline failure event. The indicators credit rating downgrades, falling share prices are identified as the most important for the effective improvement of reputation loss in pipeline failure event. Highlights: The reputation loss should be paid great attention to when considering the consequences assessment of pipeline failure. The structure of the reputation loss factors and indicators in pipeline failure event is presented. The Calculating procedure for the key indicators for reputation loss in oil and gas pipeline failure event is proposed. The weights and rankings of the reputation loss factors and indicators in pipeline failure event are performed.